MAQASHID SYARI’AH SEBAGAI EPISTEMOLOGI PENDIDIKAN PANCASILA - Ahmad Fahri Yahya Ainuri (Jurnal Progress)
Abstract As Indonesian people, of course we are familiar with religious groups with transnational ideologies that are oriented towards replacing government systems with Islamic systems (Imamat / Khilafah) based on the Qur'an and Hadith. Actually there is nothing wrong with the group's vision because the khilahfah system is a product of ijtihad of the predecessor ulama and normatively does not contradict Islamic law. It's just that the effort to coerce to change the law which has become a collective agreement in a country can legally be said as an act of rebellion and the act is not constitutionally justified. To address this phenomenon, the writer wants to give an understanding that implicitly our country (Indonesia) has actually implemented laws that are in accordance with Islamic sharia because the Pancasila ideology which is used as a national and state paradigm is fully in line with the sharia maqashid as contained in the Koran 'and Hadith which fully aims to educate people to become human beings who are deified, humane, united, just manifested into a common life (social life). Keywords: Islamic maqashid, Epistemology, Pancasila Education.